RETRACTED: Factors of sustainable development of labour productivity in capital repairs in the Russian Federation and the EU - Fatullaev Rustam; Borovkova Anastasia; Lotkin Viktor; Sedov Dmitry (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001